The effect of the reciprocal teaching model on the ability to write explanatory texts - Santi, Novi; Parlina, Iin; Alia; Susanti, Erna (Universitas Jambi, Indonesia, 2025)
This research aims to determine and describe the influence of the reciprocal teaching model on the ability to write explanatory texts. This research employed a pre-experimental using a one-group pretest-posttest design. The population was all the seventh-grade students of Madrasah Tsanawiyah Negeri 1 Ogan Komering Ilir. The sample in this research was one class, VIIC, with 30 students. The data collection technique used was a performance test written in explanatory text. Before receiving instruction using the reciprocal teaching model, the test results showed a score of 64.93 for the ability to write explanatory text. After learning to listen through the reciprocal teaching model, the score increased to 79.10. The data shows the average test results for the ability to write explanatory texts before being taught using the reciprocal teaching model and after being taught to listen using a higher reciprocal teaching model, namely 79.10>64.93. Based on the analysis results, it shows that t-test 8.357 > t-table 1.699 with a validity degree of 29 (df 29) with a significance probability below <0.05. The results mean that H0 is rejected, and Ha is accepted.